Pathways of DNA Transfer to Plants from Agrobacterium tumefaciens and Related Bacterial Species - Lacroix, Benoît (Annu Rev Phytopathol, 2019)
Genetic transformation of host plants by Agrobacterium tumefaciens and related species represents a unique model for natural horizontal gene transfer. Almost five decades of studying the molecular interactions between Agrobacterium and its host cells have yielded countless fundamental insights into bacterial and plant biology, even though several steps of the DNA transfer process remain poorly understood. Agrobacterium spp. may utilize different pathways for transferring DNA, which likely reflects the very wide host range of Agrobacterium. Furthermore, closely related bacterial species, such as rhizobia, are able to transfer DNA to host plant cells when they are provided with Agrobacterium DNA transfer machinery and T-DNA. Homologs of Agrobacterium virulence genes are found in many bacterial genomes, but only one non-Agrobacterium bacterial strain, Rhizobium etli CFN42, harbors a complete set of virulence genes and can mediate plant genetic transformation when carrying a T-DNA-containing plasmid.